LOCAL LITERATURE AND CHILD CHARACTER DEVELOPMENT - Martha Maspaitella; Betsi Rooroh; Adisti Primi Wulan (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
This study describes the relationship of local literature and children's character, withthe anecdotal text of the Kiud as the source of the study. The results show that notonly serious children's literature is loaded with character education but ridiculous andfunny anecdotal texts also shape the character of the child. These character valuesbecome a force that enables children to behave appropriately in various socialsituations